2009
DOI: 10.3111/13696990903475833
|View full text |Cite
|
Sign up to set email alerts
|

Workplace productivity, employment issues, and resource utilization in patients with bipolar I disorder

Abstract: Bipolar I disorder is associated with a negative effect on work productivity and resource utilization and is an appropriate disease management target for employers and healthcare decision makers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 18 publications
2
28
0
Order By: Relevance
“…In a recent study, McMorris et al. found that workers with BD had lower levels of work productivity, were more likely to miss work, have reduced working hours due to medical or mental health issues, receive disability payments, be insured or covered by Medicare, and to have been fired or laid off. This impact was similar across genders, which is not the case for depression, where work capacity is reduced to a greater extent in females.…”
Section: Impact Of Bd: the Multiple Facets Of A Complex Disordermentioning
confidence: 99%
“…In a recent study, McMorris et al. found that workers with BD had lower levels of work productivity, were more likely to miss work, have reduced working hours due to medical or mental health issues, receive disability payments, be insured or covered by Medicare, and to have been fired or laid off. This impact was similar across genders, which is not the case for depression, where work capacity is reduced to a greater extent in females.…”
Section: Impact Of Bd: the Multiple Facets Of A Complex Disordermentioning
confidence: 99%
“…Instead of Remunerative Employment, the experts decided to select Acquiring, Keeping and Terminating a Job because features of employment, such as ''accepting employment'', ''advancing through a job'' or ''leaving a job in an appropriate manner'', contained in the description of this ICF category, better describe the employment experience of persons with BD. The literature in this field reports that, compared with persons with other psychiatric disorders, persons with BD have elevated rates of sustained unemployment, absenteeism and poor work performance [70][71][72][73]. These problems seem to be more associated with the depressive than with the manic phase [74,75].…”
Section: Icf Code Icf Category Titlementioning
confidence: 94%
“…Career problems of these patients are different from others, and they have their own career problems [8] including: having more absenteeism from work than other mental patients [9,10], having prolonged and sustained unemployment [11,12,13,14], having low work productivity [15,16], having high rate of termination of the employment contract [17], imposing a signi cant nancial burden on employers [15], getting a stigma in the workplace [18,15,19], having decreased number of hours worked [16,20], lack of insurance or covering by Medicare [16], getting red or laying off [21,22,16] and sliding in occupational statues [9].…”
Section: Introductionmentioning
confidence: 99%